Drug utilization study in genitourinary infections used as a teaching tool for rational therapy for MBBS students in a Medical College at Dehradun, Uttarakhand - Dutta, Shakti B.; Beg, Mirza A.; Bawa, Shalu; Kaur, Amanjot (International Journal of Basic & Clinical Pharmacology, 2017)
Background: There is a need to introduce clinical pharmacology at the undergraduate level in order to improve rational prescribing of medicines. The present study was undertaken to analyze drug utilization pattern of genitourinary infections to teach certain basic skills to MBBS students which will form an integral component of practicing rational therapeutics. Methods: The retrospective study was conducted by Pharmacology Department in Shri Guru Ram Rai Institute of Medical and Health Sciences (SGRRIM and HS). A total of 92 prescriptions were collected by second professional MBBS students and randomly evaluated for prescribing pattern using WHO drug indicators. Results: A total of 92 prescriptions were analyzed. Male:female ratio was 1.96:1. Age wise distribution was done: 0-15 years were 14 (15.21%), 16-30 years were 26 (28.26%), 31-45 years were 24 (26.08%), 46-60 years were 19 (20.65%), and >60 years were 9 (9.78%). A total of 260 drugs were prescribed. 116 (44.61%) antimicrobials, 70 (26.92%) antacids and antiemetics, 40 (15.38%) analgesics, 11 (4.23%) urinary alkalizers, 9 (3.23%) antifibrinolytics, and 14 (5.38%) miscellaneous drugs were prescribed. 144 (55.38%) injectable and 116 (44.61%) oral drugs were prescribed. Numbers of fixed-dose combinations were 32 (34.78%). 2.82 drugs per prescription were prescribed. 171 (65.76%) drugs were prescribed from National List of Essential Medicines 2013 (NLEM 2013). Majority of drugs were prescribed by brand names. Conclusion: Majority of drugs were prescribed from NLEM 2013. The main purpose of undergraduate medical curriculum is to develop the requisite diagnostic and therapeutic skills of a basic doctor. It is only by drug utilization studies that burden of diseases and corresponding utilization of drugs can be measured.